2015
DOI: 10.1111/asj.12539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of porcine oocytes on the expression levels of transcripts encoding glycolytic enzymes in granulosa cells

Abstract: Oocytes play critical roles in regulating the expression of transcripts encoding the glycolytic enzymes phosphofructokinase, platelet (PFKP) and lactate dehydrogenase A (LDHA) in granulosa cells in mice, but whether this is the case in pigs or other mammals has not been adequately investigated. Therefore, the aim of this study was to determine whether porcine oocytes regulate the expression levels of these transcripts in granulosa cells in vitro. Porcine cumulus cells expressed higher levels of PFKP and LDHA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It was also reported that low oxygen stimuli in mice enhanced the expression of glycolytic genes in GCs, as well as the survival rate and development of follicles [ 28 ]. Furthermore, oocytes themselves activate glycolytic genes through the secretion of cytokines in mice and pigs [ 29 , 30 , 31 ]. Contrary to the activation of glycolysis, hypoxic conditions decreased mitochondrial functions and quantity, as determined by mitochondrial mass and DNA copy number [ 27 ].…”
Section: Molecular Background Of Granulosa Cell Proliferationmentioning
confidence: 99%
“…It was also reported that low oxygen stimuli in mice enhanced the expression of glycolytic genes in GCs, as well as the survival rate and development of follicles [ 28 ]. Furthermore, oocytes themselves activate glycolytic genes through the secretion of cytokines in mice and pigs [ 29 , 30 , 31 ]. Contrary to the activation of glycolysis, hypoxic conditions decreased mitochondrial functions and quantity, as determined by mitochondrial mass and DNA copy number [ 27 ].…”
Section: Molecular Background Of Granulosa Cell Proliferationmentioning
confidence: 99%
“…Real‐time PCR analysis was conducted as reported previously (Matsuno et al., 2016). In brief, total RNA was extracted from MGCs using a ReliaPrep TM Cell Miniprep System (Promega KK), and reverse transcribed using a ReverTraAce qPCR Master Mix with gDNA Remover (Toyobo, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Porcine COCs and MGCs were collected from antral follicles 2–5 mm in diameter as previously reported [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Real-time PCR analysis was conducted as previously reported [ 25 ]. Briefly, total RNA was extracted from COCs using a ReliaPrep TM Cell Miniprep System (Promega) and reverse-transcribed using a ReverTraAce qPCR Master Mix with gDNA Remover (Toyobo, Osaka, Japan) according to the manufacturer′s protocols.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation